2021
DOI: 10.3390/catal11091051
|View full text |Cite
|
Sign up to set email alerts
|

Oleate Hydratase from Lactobacillus rhamnosus ATCC 53103: A FADH2-Dependent Enzyme with Remarkable Industrial Potential

Abstract: Recently, we described the preparation of the recombinant oleate hydratase from Lactobacillus rhamnosus ATCC 53103. We observed that the purified C-terminal His-tagged enzyme was completely inactive and the catalytic activity was partially restored only in presence of a large amount of flavin adenine dinucleotide (FAD). In the present work, we assess that this hydratase in the presence of the reduced form of flavin adenine dinucleotide (FADH2) is at least one hundred times as active as in the presence of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…For the oleic acid hydration (upstream), reaction conditions reported in the literature, which are believed to be close to industrial applications, were retrieved. [36][37][38] An aqueous solution was employed as reaction medium, with a co-solvent mixture composed of glycerol (8%, v/v) and ethanol (2%, v/v). Under these conditions, it is reported that 10-HSA precipitates in the form of a white solid.…”
Section: Case Study: Oleic Acid Hydration Catalyzed By Oleate Hydrata...mentioning
confidence: 99%
See 2 more Smart Citations
“…For the oleic acid hydration (upstream), reaction conditions reported in the literature, which are believed to be close to industrial applications, were retrieved. [36][37][38] An aqueous solution was employed as reaction medium, with a co-solvent mixture composed of glycerol (8%, v/v) and ethanol (2%, v/v). Under these conditions, it is reported that 10-HSA precipitates in the form of a white solid.…”
Section: Case Study: Oleic Acid Hydration Catalyzed By Oleate Hydrata...mentioning
confidence: 99%
“…Under these conditions, it is reported that 10-HSA precipitates in the form of a white solid. [36][37][38] Herein, for downstream processing, three scenarios were considered: (i) simple filtration of the precipitated 10-HSA, which is just washed with water and dried; (ii) as the precipitated 10-HSA contains some traces of oleic acid, a subsequent recrystallization step is suggested, using hexane : ethyl acetate (2 : 1); and (iii) in a different approach, acidification of the reaction media with HCl and extraction of 10-HSA using ethyl acetate (3×), and subsequent addition of different chemicals (NaCl, Celite, sulphates) to render pure 10-HSA were performed (Fig. 1).…”
Section: Case Study: Oleic Acid Hydration Catalyzed By Oleate Hydrata...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the Cp_sc-CO 2 A fraction was also subjected to a biocatalyzed hydration exploiting the activity of the recombinant oleate hydratase from Stenotrophomonas maltophilia (OhyA2), an enzyme showing high activity as well as a broad substrate scope [ 58 ]. Similarly to other oleate hydratases [ 28 , 59 , 60 ], OhyA2 showed excellent performances when used in a reducing environment. Accordingly, Cp oil (20 g L − 1 ) was incubated with OhyA2 (0.1 g L − 1 ) in the presence of Ti III -citrate as reducing agent for 24 h at 35 °C, thus promoting the complete conversion of the two most abundant UFAs, i.e., oleic acid and linoleic acid ( Table 2 ), into the corresponding 10-hydroxy derivatives ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 93%
“…Specifically, members of the fatty acid ethanolamide family, such as arachidonylethanolamide (AEA, also known as anandamide), oleoylethanolamide (OEA), and palmitoylethanolamide (PEA), show a variety of biological activities, e.g., anti-inflammatory, anorexic effects—useful for appetite control in people with obesity—and analgesic effects [ 24 , 25 ]. On the other side, hydroxy fatty acids (HFAs), obtained by hydration of unsaturated fatty acids (UFAs), are important precursors of flavors, biodegradable polymers, lubricants, cosmetic ingredients, and emulsifiers [ 26 , 27 , 28 , 29 ]. Both enzymatic reactions were first optimized by selection of the respective biocatalyst and biotransformation conditions using standard fatty acids as substrates, then applied to the fatty acid-enriched Cp extracts.…”
Section: Introductionmentioning
confidence: 99%